2018
DOI: 10.4172/2471-8416.100049
|View full text |Cite
|
Sign up to set email alerts
|

Visual Loss After Lateral Position Total Hip Arthroplasty: A Case Report

Abstract: Perioperative visual loss (POVL) is an infrequent, devastating complication. Increased recognition and discussion of this complication is reported in recent literature, most notably following spinal and cardiac surgery. The most common causes are ischemic optic neuropathy, central retinal artery occlusion, and cortical blindness. Here, we present a case of a 54 y old female who developed acute visual loss in her eyes after lateral position total hip arthroplasty that might explain this complication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
(12 reference statements)
0
2
0
Order By: Relevance
“…Of the various causes of POVL, three main groups of pathologic entities have been identified that may be responsible for POVL ischemic optic neuropathy (ION), central retinal artery occlusion (CRAO) and cortical blindness. 1 , 2 , 3 , 4 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the various causes of POVL, three main groups of pathologic entities have been identified that may be responsible for POVL ischemic optic neuropathy (ION), central retinal artery occlusion (CRAO) and cortical blindness. 1 , 2 , 3 , 4 …”
Section: Discussionmentioning
confidence: 99%
“…PION comprises 3 types:arteritic PION, non-arteritic PION, and surgical PION as a complication of several systemic surgical procedures 1 , 2 , 3 , 4 …”
Section: Discussionmentioning
confidence: 99%